Pendidikan Intercultural: Solusi Bullying di Lingkungan Pendidikan Indonesia - Dewi, Lharasati; Abdillah, Muhamad Hasan (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Bullying is a severe problem in many countries, including Indonesia. Data recorded by KPAI from 2011 to 2019, bullying is still a case of violence that dominates in the world of education. This paper aims to offer the application of intercultural education to minimize and prevent bullying in the educational environment. The method used is a literature review by collecting previous research results from journals, supporting theories from books, and some field data published in newspapers' digital media. The result is that the application of intercultural education has made a positive contribution in various countries, such as creating values of unity and understanding between cultural diversity to be accepted. Thus, it can be concluded that intercultural education can be a solution to building a positive environment and shaping the character of individuals and communities full of compassion.